CTCF: a Swiss-army knife for genome organization and transcription regulation. Issue 1 (2nd April 2019) - Braccioli, Luca; de Wit, Elzo
Abstract : Orchestrating vertebrate genomes require a complex interplay between the linear composition of the genome and its 3D organization inside the nucleus. This requires the function of specialized proteins, able to tune various aspects of genome organization and gene regulation. The CCCTC-binding factor (CTCF) is a DNA binding factor capable of regulating not only the 3D genome organization, but also key aspects of gene expression, including transcription activation and repression, RNA splicing, and enhancer/promoter insulation. A growing body of evidence proposes that CTCF, together with cohesin contributes to DNA loop formation and 3D genome organization. CTCF binding sites are mutation hotspots in cancer, while mutations in CTCF itself lead to intellectual disabilities, emphasizing its importance in disease etiology. In this review we cover various aspects of CTCF function, revealing the polyvalence of this factor as a highly diversified tool for vertebrate genome organization and transcription regulation.